A pencil distributed direct numerical simulation solver with versatile treatments for viscous term. (15th October 2021) - Gong, Zheng; Fu, Xudong
Abstract: We present an efficient second- or fourth-order finite difference direct numerical simulation (DNS) solver using pencil-like domain decomposition parallel strategy, with the ability to handle different boundary conditions. The viscous term is treated implicitly, partial implicitly, or explicitly. The runtimes for different viscous treatments and different boundary conditions are evaluated quantitatively, which can help us to get a fast computational speed for specific flow cases. FFT-based method is used for solving Pressure Poisson equation, and alternating direction implicit approach is adopted for Helmholtz equations during the implicit viscous treatment. The numerical results achieve good match with those obtained from spectral methods. In addition, the resulting solver exhibits quite good parallel efficiency, and demonstrates good computational speedup and versatility than other pencil-like DNS solvers reported in the literature. The source code is freely available at https://github.com/GongZheng-Justin/Channel3d .